Phase coherence theory for data-mining and analysis: application studies in spectroscopy - PEROVA, TANIA; MOORE, ALAN (SPIE, 2005)
The paper investigates from the perspective of computer science the phase coherence theory (PCT) and phase coherent data-scatter (PCD-S). These techniques were originally developed for the area of optical tensiographic data mining and analysis but have a more general application in data mining. These developments have recently been augmented with the engineering of a software toolkit called TraceMiner. Although the toolkit was originally devised for tensiography it was developed to perform as a generic data mining and analysis application with PCT, PCD-S and a range of other data mining algorithms implemented. To date the toolkit has been utilised in its main application area, tensiography, but has also been applied to UV-visible spectroscopy. This work presents a critical investigation of the general utility of PCT, PCD-S and the toolkit for data mining and analysis. A new application of PCT and the TraceMiner software toolkit to Raman spectroscopy is presented with discussion of the relevant measures and the information provided by the toolkit. This provides more insight into the generic potential of the techniques for data mining. The analysis performed on theoretical Raman data is augmented with a study of experimental Raman data. Raman spectroscopy is used for composition and fault detection analysis in semiconductor surfaces. Finally, the utility of the PCT technique in comparison with traditional Raman spectroscopy methods is considered together with some more general applications in the field of imaging and machine vision.
PUBLISHED
Keywords: Electronic & Electrical Engineering